The Effect of Trade Liberalization on Economic Growth, Unemployment and Productivity: The Case of Jordan - Alamro, Hassan (International Review of Management and Marketing, 2017)
This study aims to investigate the impact of trade liberalization on Jordan's economic growth through examining improvement in employment and productivity in Jordan, during the period (1980-2014). Where Augmented Dickey- Fuller test was utilized to examine the stationary of the variables of this study. The results have indicated that the variables are non-stationary at their levels, but they become stationary at their first difference. Also Johansen cointegration test was applied, and it was found there is one cointegration vector exists among the variables in the model. Vector error correction model (VECM) found a long-run relationship between real gross domestic product per capita and other variables (trade openness, unemployment rate, labor productivity). And provide the Short-term deviations from the long-term equilibrium relationship are corrected at a rate (0.25). Furthermore VECM showed a positive and significant impact from the explanatory variables on economic growth of Jordan in the long run, and non-significant impact in the short run. On the other hand, the impulse response function and variance decomposition test indicated that a positive impact from trade liberalization on economic growth, labor productivity and unemployment rate. Keywords: Trade Liberalization, Economic Growth, Productivity, Unemployment, Vector Error Correction Model JEL Classifications: F4, O4